Food price shocks and the political economy of global agricultural and development policy - Johan Swinnen; Andrea Guariso; Mara P. Squicciarini (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2014)
The recent spikes of global food prices induced a rapid increase in mass media coverage, public policy attention, and donor funding for food security, and for agriculture and rural poverty. This has occurred while the shift from "low" to "high" food prices has induced a shift in (demographic or social) "location" of the hunger and poverty effects, but the total number of undernourished and poor people have declined over the same period. We discuss whether the observed pattern can be explained by the presence of a "global urban bias" on agriculture and food policy in developing countries, and whether this "global urban bias" may actually benefit poor farmers. We argue that the food price spikes appear to have succeeded where others have failed in the past: to move the problems of poor and hungry farmers to the top of the policy agenda and to induce development and donor strategies to help them.
Keywords: 330; Lebensmittelpreis; Preisniveau; Armut; Medienwirkung; Entwicklungshilfe; Entwicklungsländer